Digital Leadership Transformation in the Modern Era: Empowering Aisyiyah Mothers through Social Media - Faroek, Dewi Astria; Ermin, Ermin; Rezki, Rezki; Muslimah, Virasanty; Fakhri, La Jupriadi; Miswar, Nur (UNIVERSITAS MUHAMMADIYAH MATARAM, 2024)
The community service program is an activity carried out to contribute to the community directly with the main objective of increasing understanding to the participants about digital leadership and providing direct training in the use of social media as a medium for da'wah. This activity was held at Nawa Flat, Sorong City, on September 16, 2024, attended by 30 Aisyiyah women participants. This activity was carried out offline in one meeting session using material delivery using the lecture method, question and answer sessions and direct training on the use of social media as a preaching medium using the Tiktok and Canva applications. The results obtained show an increase in participants' understanding and skills in utilizing digital technology for da'wah purposes. This program has an important meaning in empowering Aisyiyah women to be able to use social media effectively, so that it is expected to expand the reach of da'wah messages in the digital era.